Indian community-based housing finance systems: potentials and pitfalls for urban development and housing improvement. Issue 4 (2nd October 2019) - Smets, Peer
ABSTRACT: In developing and emerging countries, housing finance is mainly mortgage finance in combination with Western unsecured credit, both of which do not serve the bottom of the income pyramid. Poorer sections of society depend on incremental finance for building their houses. A combination of different sources is usually used including individual servicing of housing finance and community-based housing finance. Community-based financing covers a relatively small section of the housing finance market. In the formal financial sector, such initiatives include mainly credit unions and cooperatives. In the informal sector, a much broader kaleidoscope of community-based financing schemes and links with banks exists. This paper provides an overview of three kinds of informal community-based housing finance associations: rotating savings and credit associations, savings associations and accumulating savings and credit associations. These examples can be seen as a source of good practices. However, schemes that are commodified can have a huge potential for the development of informal settlements, but can also become instruments of institutions, benefiting the state and the better off, who profit at the expense of those at the bottom of the income pyramid.